Refining the Production Date of Historical Palestinian Garments Through Dye Identification - Diego Tamburini; Ludovic Durand; Zeina Klink-Hoppe (Heritage)
The dyes used to produce two Palestinian garments from the British Museum’s collection attributed to the late 19th–early 20th century were investigated by high pressure liquid chromatography coupled with diode array detector and tandem mass spectrometry (HPLC-DAD-MS/MS). Palestinian embroidery is a symbol of national identity and the topic of scholarly research. However, little attention has been given to the dyes and how these changed with the introduction of new synthetic formulations in the second half of the 19th century. The results revealed the use of natural indigoid blue and red madder (Rubia tinctorum), in combination with tannins. Yellow from buckthorn (probably Rhamnus saxatilis) and red from cochineal (probably Dactylopius coccus) were found mixed with synthetic dyes in green and dark red embroidery threads, respectively. Early synthetic dyes were identified in all the other colours. These include Rhodamine B (C.I. 45170), Orange II (C.I. 15510), Orange IV (C.I. 13080), Metanil Yellow (C.I. 13065), Chrysoidine R (C.I. 11320), Methyl Violet (C.I. 42535), Malachite Green (C.I. 42000), Fuchsin (C.I. 42510), Auramine O (C.I. 41000) and Methyl Blue (C.I. 42780). As the date of the first synthesis of these dyes is known, the production date of the garments was refined, suggesting that these were likely to be produced towards the end of the 1880s/beginning of the 1890s. The continuous use of historical local sources of natural dyes, alongside new synthetic dyes, is of particular interest, adding rightful nuances to the development of textile-making practices in this region.